Does Quality of Corporate Governance affect Financial Performance of listed firms in NSE, Kenya? - Tuwey, J. Kiplagat (African Journal of Education,Science and Technology (AJEST), 2020)
The goal of this paper is to analyze the effect of corporate governance efficiency on the financial performance of listed companies in the Nairobi Securities Exchange in Kenya between 2008 and 2017. The pooled OLS estimation approach was used to evaluate the hypothesis using panel data from 650 firm year observations. Results showed that both Disclosure and Related Party transactions are positively and substantially related to financial performance. Nonetheless, legal compliance was negatively and strongly linked to financial performance. The results provide empirical evidence that there is a link between CG quality and financial performance in Kenya. These findings are relevant for financial regulators such as CMA in their efforts to improve corporate governance practices in Kenya.